PENGARUH PERLAKUAN PANAS BAJA AISI 1029 DENGAN MEDIA PENDINGIN AIR DAN OLI TERHADAP KEKUATAN DAN KEKERASAN - Nofriady Handra; Rio Fernando (LP2M - Institut Teknologi Padang, 2014)
The process of heat treatment is a combination of the operation of heating and cooling with certain speed and was conducted on metal or alloyed in the solid state as an attempt to acquire the nature of certain properties. The temperature of the warming is done for 7850 C and 8200 C. As for the purpose of this research is to find out how the mechanical properties of steel heat treatment at different temperatures and then to find out the value of the strength and hardness of steel with optimal cooling water and oil media. research methods used are experimental methods, experimental group consisted of samples which have been subjected to heat treatment which is pull-test sample amounted to 13 sample afterward for comparison is 3 samples. How does the difference in strength and violence that occurred after the heat treatment was given with water cooling and oil media against material that had not been given the treatment. From the test results and calculations made on the influence of heat treatment of Steel AISI 1029 with water cooling and oil mediums of the strength and hardness, the highest strength values found in the samples that were given a heat treatment at a temperature of 8200 C with the value of the strength value then Mpa 972 highest violence also occurs in the sample who were given preferential treatment at a temperature of 8200 C with 299 VHN.